2013
DOI: 10.1097/coc.0b013e318210f83c
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare, clinically aggressive cutaneous neuroendocrine neoplasm with a high mortality rate. Though the etiology is not precisely known, Merkel cell polyomavirus (MCV) DNA has been found recently in a large percentage of MCC tumors. Other suggested risk factors include sun-exposure, immunosuppression and a history of prior malignancy. Work-up of patients with MCC most notably includes nodal staging via clinical exam or sentinel lymph node biopsy (SLNB). The prognosis for most pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 107 publications
0
54
0
Order By: Relevance
“…MCC has propensity for early spread and recurrence and while surgery and radiotherapy can achieve high rates of locoregional control, chemotherapy rarely provides durable responses for distant metastatic disease (4). The deployment of improved targeted therapies is likely to be achieved through a better understanding of MCC biology.…”
Section: Introductionmentioning
confidence: 99%
“…MCC has propensity for early spread and recurrence and while surgery and radiotherapy can achieve high rates of locoregional control, chemotherapy rarely provides durable responses for distant metastatic disease (4). The deployment of improved targeted therapies is likely to be achieved through a better understanding of MCC biology.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, adjuvant RT is advocated because MCC has a high incidence of nodal and metastatic disease. 27,28 A previously unaddressed question was whether RT was beneficial in those patients specifically known to be node negative. Our study found that there was no statistical survival advantage to giving adjuvant RT to patients with a negative SLNB.…”
Section: Commentsmentioning
confidence: 99%
“…Current optimal treatment is with radical surgical excision of the primary tumour, sentinel lymph node biopsy, ± regional lymph node dissection, radiotherapy, chemotherapy & immunotherapy [10,39,40].…”
Section: Treatmentmentioning
confidence: 99%